Studies to identify an alternative aphid host for culturing the predatory syrphid, Ischiodon scutellaris (Fabricius) (Diptera: Syrphidae) - Amala Udayakumar; K. G. R. Chandramanu; Sunil Joshi; Timalapur M. Shivalingaswamy (Egyptian Journal of Biological Pest Control, 2023)
Abstract Background Aphidophagous syrphid, Ischiodon scutellaris (Fabricius) (Diptera: Syrphidae) is an effective predator of aphids that infest many agricultural and horticultural crops. Cowpea aphid, Aphis craccivora Koch (Hemiptera: Aphididae), is the natural host for culturing syrphid predator, I. scutellaris. The present study was conducted to evaluate the feeding and development of I. scutellaris on seven species of aphid hosts viz., A. craccivora, Aphis fabae Scopoli, Aphis gossypii Glover (from cotton), Schoutedenia emblica (Patel & Kulkarni), Brevicoryne brassicae (L.), Aphis gossypii (from okra) and Hyperomyzus carduellinus (Theobald) and to identify an alternative aphid host to maintain the culture of I. scutellaris during the situation of non-availability/loss of the culture of A. craccivora. Results Aphis fabae was not accepted for feeding by the larvae of I. scutellaris. The larvae of I. scutellaris did not survive on S. emblica. The descending order of feeding potential of aphids by I. scutellaris was A. craccivora > H. carduellinus > B.brassicae > A. gossypii (from cotton) > A. gossypii (from okra) > S. emblica. The larva of I. suctellaris completed its development in combination of the aphid prey (A. craccivora + H. carduellinus). The net reproductive rates (R 0) of I. scutellaris when fed on A. craccivora and H. carduellinus were 308.28 and 302.33, respectively. The intrinsic rate of increase (r) of I. scutellaris was significantly higher when reared on H. carduellinus (0.155 ± 0.003) than on A. craccivora (0.143 ± 0.004). Conclusion The results confirmed that H. carduellinus reared on Lactuca virosa could serve as an alternate host for the mass production of I. scutellaris.